Eufemisme Oleh Pendakwah Dalam Dialek Negeri Sembilan - Khazri Osman; Mohamad Yazid Abdul Majid; Melor Fauzita Md Yusoff; Mohammad Fadzeli Jaafar; Sharifah Nuraina Nabila Syed Sharifuddin (Usuli Faqih Research Centre PLT, 2025)
Indexed by MyCite